2013
DOI: 10.1007/s10815-013-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of granulosa cells: on the crossroad of stemness and transdifferentiation potential

Abstract: The ovarian follicle represents the basic functional unit of the ovary and consists of an oocyte, which is surrounded by granulosa cells (GCs). GCs play an important role in the growth and development of the follicle. They are subject to increased attention since it has recently been shown that the subpopulation of GCs within the growing follicle possesses exceptionally plasticity showing stem cell characteristics. In assisted reproduction programs, oocytes are retrieved from patients together with GCs, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 88 publications
(97 reference statements)
1
42
0
Order By: Relevance
“…Thus, it is plausible that granulosa cells or pregranulosa cells contained within existing follicles are the source of new material for freshly formed follicles. While granulosa cells may not indeed be ‘stem cells’ based on characteristics such as asymmetric division or indefinite self-renewal, granulosa cells obtained from human follicular aspirates and cumulus cells, or from porcine antral follicles have been described as having a multi-potent molecular signature, and have been reported to express genes associated with pluripotency such as POU domain, class 5, transcription factor 1 (Pou5f1), Nanog Homeobox (Nanog), SRY (sex determining region y)-box 2 ( Sox2 ), and telomerase reverse transcriptase ( TERT ), although there is some inconsistency in gene expression patterns reported which may be due to methodological differences in sample collection and/or species (Kossowska-Tomaszczuk et al, 2009; Mattioli et al, 2012; Varras et al, 2012; discussed in Dzafic et al, 2013). Additionally, following prolonged culture under defined conditions similar to those used to maintain other adult stem cell types, human granulosa-luteal cells spontaneously de-differentiate, and progressively lose the steroidogeneic capacity associated with their terminally differentiated phenotype while acquiring the mesenchymal stem cell markers CD29, CD44, CD90, CD105, CD117, and CD166 (Kossowska-Tomaszczuk et al, 2009).…”
Section: Granulosa Cells: Origin and Plasticitymentioning
confidence: 99%
“…Thus, it is plausible that granulosa cells or pregranulosa cells contained within existing follicles are the source of new material for freshly formed follicles. While granulosa cells may not indeed be ‘stem cells’ based on characteristics such as asymmetric division or indefinite self-renewal, granulosa cells obtained from human follicular aspirates and cumulus cells, or from porcine antral follicles have been described as having a multi-potent molecular signature, and have been reported to express genes associated with pluripotency such as POU domain, class 5, transcription factor 1 (Pou5f1), Nanog Homeobox (Nanog), SRY (sex determining region y)-box 2 ( Sox2 ), and telomerase reverse transcriptase ( TERT ), although there is some inconsistency in gene expression patterns reported which may be due to methodological differences in sample collection and/or species (Kossowska-Tomaszczuk et al, 2009; Mattioli et al, 2012; Varras et al, 2012; discussed in Dzafic et al, 2013). Additionally, following prolonged culture under defined conditions similar to those used to maintain other adult stem cell types, human granulosa-luteal cells spontaneously de-differentiate, and progressively lose the steroidogeneic capacity associated with their terminally differentiated phenotype while acquiring the mesenchymal stem cell markers CD29, CD44, CD90, CD105, CD117, and CD166 (Kossowska-Tomaszczuk et al, 2009).…”
Section: Granulosa Cells: Origin and Plasticitymentioning
confidence: 99%
“…To test this hypothesis, we observed that cell death in the ischemic model was only observed in the HGL5 cell line in which p53, a key factor in the maintenance of genomic stability, was not detected. In vivo, granulosa cells displayed different properties related to their localization and function around the oocyte [45]. Therefore, it is not very surprising that the three different cell lines display different responses to stress injuries.…”
Section: Gc1amentioning
confidence: 99%
“…Flattened or cubic layer granulosa cells (the membrana granulosa) of primordial and primary follicles are positively stained for nuclear membrane Lamin A, but negative for proliferative markers PCNA or Ki67 [51][52][53][54], and the membrana granulosa cells are considered as differentiated cells, and these features also are consistent with their dormant state as follicle reservoir. On the contrary, many granulosa cells underneath the theca cells in the secondary growing and antral follicles show positive staining for PCNA or Ki67 but negative for Lamin A, and these granulosa cells exhibit stem cells-like property [6,26]. High levels of BRCA1 expression in the proliferative stem-like cells could also help repair DSBs accumulated in the middle-age monkey ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere length in cumulus cells may serve as a biomarker of oocyte and embryo quality [25]. Although granulosa cells show characteristics of somatic stem cells [6,26], these cells still undergo telomere shortening with age [27], possibly due to long-term exposure to reactive oxygen species, impairment in cellular physiology and gradual decreasing numbers of follicles [28]. Stem cell dysfunction provoked by telomere shortening may be one of the mechanisms responsible for organismal aging in both humans and mice [29].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%